Stress adaptions of the resurrection fern Anemia caffrorum's microbiome and metabolism across seasons - Wittenberg, Michael (Department of Molecular and Cell Biology, 2025)
Resurrection plants can tolerate desiccation for extended periods of time. So far, Anemia caffrorum is the only known resurrection plant which exhibits this phenomenon seasonally. In the wet season, its fronds are desiccation sensitive (DS) whilst in the dry season they are desiccation tolerant (DT) and can survive losing more than 95% of their cellular water content. Its rhizome on the other hand is tolerant all year round and likely regulates the tolerance of the fronds. As such, it provides a unique model to contrast desiccation sensitivity and tolerance within the same plant species. Furthermore, previous transcriptomic and metabolomic analyses on the rhizome suggested that it attempts to modulate its microbiome during desiccation and its response to pathogenic microorganisms during the wet season. Therefore, in this study, A. caffrorum was used as a model to identify microorganisms associated with either plant desiccation sensitivity or tolerance and characterize their dynamics in response to fluctuations in water content and across seasons. Furthermore, to identify potential signaling or selection mechanisms between A. caffrorum and its associated microorganisms, matching metabolomics was conducted. Additionally, this allowed for the characterization of the metabolic mechanisms of desiccation tolerance employed by A. caffrorum and its associated microbes. To this end, the root endosphere, rhizosphere and bulk soil controls were sampled from A. caffrorum in its natural environment across seasons. This captured samples from hydrated DS individuals as well as desiccated and rehydrated DT individuals. In order to characterize their bacterial and fungal compositions, genomic DNA extracts of all samples were subjected to 16S and ITS amplicon sequencing on a PacBio Sequel II platform. In addition, polar metabolites and lipids were measured from these samples using combinations of untargeted Gas and Liquid Chromatography Mass Spectrometry. The results showed that indeed A. caffrorum can enrich its endosphere with beneficial taxa such as symbiotrophs whilst excluding pathogens. Furthermore, A. caffrorum can shape its microbiome across seasons and changing water contents to respond to stress. In the hydrated state, particularly in the DS individuals, biotic stress appeared to be prioritized as these samples exhibited numerous pathogenic, antibiotic producing and antibiotic resistant taxa in addition to antibiotic metabolites. In addition, a number of growth promoting bacteria were found to be increased in these hydrated samples which may assist A. caffrorum with growth processes during water availability. In response to desiccation, triacylglycerols and phospholipids were accumulated. Moreover, simple monosaccharides were likely mobilized to more complex desiccation protective di- and trisaccharides. This shift may have selected for an increase of glycolytic and saprobic taxa. Such functionalities may be beneficial to A. caffrorum during desiccation and potentially allow for rapid remobilization of nutrients upon rehydration. Network analysis within the endosphere identified that microbes were generally most linked to lipid metabolism. Here the antibiotic producer Dactylosporangium was the top taxa influencing network topology and was exclusively correlated to numerous lyso phospholipids which are known as signaling molecules involved in inter alia the plant immune response. Thus, A. caffrorum may efficiently regulate its microbiome by acting on influential antibiotic producing taxa. These findings, if validated through further studies, highlight possible mechanisms through which crops may also modulate their microbiomes in response to stress. This could contribute to ensuring food security under increasing climate change driven biotic and abiotic stress